Keys of the kingdom - Mankiewicz, Joseph L. 1909-1993; Stahl, John M. 1886-1950 (20th Century Fox Home Entertainment, 1944)
After losing his parents and his childhood sweetheart to tragedy. Francis Chisholm (Peck) joins the priesthood and devotes himself to a life of service and compassion. But Chisholm's unorthodox beliefs raise eyebrows among his superiors, especially Bishop Angus Mealy (Vincent Price). And when he is sent to the farthest reaches of China to rebuild an abandoned mission. Chisholm faces his greatest challenge of all: to tame a hostile land, win over a superstitious people and save his parish from an invading army.